Urban and Community Forestry in the Northeast - Kuser, John E.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
Cover design by Susanne Van Duyne (Trade Design Group) Cover illustration depicts the USDA Plant Hardiness Zone
Origins of Urban Forestry -- Understanding the Benefits and Costs of Urban Forest Ecosystems -- Arboriculture Law in the Northeast -- Tree Ordinances -- Using Comprehensive Planning to Conserve the Natural Environment -- Urban and Community Forestry: Planning and Design -- Tree Inventory and Systematic Management -- Urban and Community Forestry Financing and Budgeting -- Community Involvement in Urban Forestry Programs -- Soils: The Key to Successful Establishment of Urban Vegetation -- Selecting Trees for Community Landscapes -- Guide to Selecting and Specifying Nursery Stock -- Planting and Maintenance -- Pruning -- Trees, Utilities, and Municipalities -- Tree Roots versus Sidewalks and Sewers -- Hazard Tree Inspection, Evaluation, and Management -- Integrated Pest Management -- Tree Appraisal: The Goal is Equity -- Leaf Composting -- Urban Tree Removals -- Recycling Urban Tree Removals -- Tree City USA -- A Case Study of Paramus, New Jersey: A "Tree City USA" Community -- Attracting and Managing for Wildlife -- Managing Urban Ecosystems: A Look to the Future of Urban Forestry.
Keywords: LIFE SCIENCES; ARCHITECTURE; FORESTS AND FORESTRY; ENVIRONMENTAL LAW; ENVIRONMENTAL MANAGEMENT; SOIL CONSERVATION; ENVIRONMENTAL ECONOMICS; LIFE SCIENCES; FORESTRY; LANDSCAPE ARCHITECTURE; ENVIRONMENTAL LAW/POLICY/ECOJUSTICE.; ENVIRONMENTAL MANAGEMENT; SOIL SCIENCE & CONSERVATION; ENVIRONMENTAL ECONOMICS